Analisis Locus of Control (LoC) terhadap Daya Saing Pelaku Usaha Mikro Kecil Menengah (UMKM) di Kota Pangkalpinang - Hamsani Hamsani; Dian Prihardini Wibawa; Ayu Wulandari (Society, 2021)
The reality shows that Micro, Small, and Medium Enterprises (MSMEs) play a very important role in economic growth. Even MSMEs are the only micro institutions that have not been shaken by the monetary crisis that began in 1988. However, as one of the mainstay sectors of society, especially the lower-middle-class economic community, the role of MSMEs has not been maximized, so they have not been able to compete fully and, even worse, many MSMEs have gone out of business or are inactive. Many factors cause the inability of SMEs to compete, among others, due to low innovation and competitiveness, so they have not been able to win competition both in the national and international spheres. The decrease in the number of MSMEs from active to inactive is because these MSMEs are less able to survive in an increasingly fierce competition arena. Only MSMEs that survive are MSMEs that have creations and innovations according to the community’s needs. The inability to create creations and innovations is suspected that most MSME actors have a personality that lacks confidence due to their low managerial ability. If MSME actors have an Internal Locus of Control and high managerial abilities, MSME actors will be more creative and innovative. This research uses a qualitative and quantitative descriptive approach descriptively and inferentially to analyze the LoC on the competitiveness of micro, small and medium enterprises (MSMEs) in Pangkalpinang City with a total sample of 50 MSMEs. The analytical tool used in this research is to use a Likert scale scoring. Multiple linear regression is performed with the competitiveness of MSMEs as the dependent variable and LoC as the independent variable. The research results stated that the Internal Locus of Control (ILoC) of MSME actors in Pangkalpinang City was higher than External Locus of Control (ELoC) and Locus of Control had a significant and positive influence on the competitiveness of MSMEs in Pangkalpinang City.